PERLINDUNGAN HUKUM TERHADAP PERUBAHAN MEREK TERKENAL MENJADI MEREK GENERIK BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 - Reni Eka Septianingrum; Adi Sulistiyono (Fakultas Hukum Universitas Sebelas Maret, 2024)
This articles aim to determine the legal protection of well-known trademark into generic trademark in the Intellectual Property Law system in Indonesia. This writing is a normative legal research with prescriptive research characteristics. Legal materials used in this research are primary and secondary legal materials that are collected by using literature study techniques. The author in conducting this research uses a statutory approach, a case approach, a conceptual approach, and a comparative approach. Based on the results of the discussion, it was concluded that a well-known registered mark that proved to be transformed into a generic brand would lose its distinguishing power, so that such a brand has weak legal protection and has the potential to face a lawsuit for cancellation. However, under certain conditions, there are marks that are indicated to have changed to become generic and still receive legal protection and remain registered, provided that the mark is able to build secondary meaning by public understanding.Generic Trademark; Legal Protection; Wellknown Trademark